Menciptakan Kerukunan Antar Dua Suku Melalui Kesenian Reog Ponorogo di Kabupaten Banyuwangi - Didit Kurniawan Wintoko; Febriyanto Hermawan; Lukman Hakim Alfaridzi (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Reog Ponorogo is a traditional dance art originating from Ponorogo. Reog art is usually used to enliven events and entertainment. Reog art itself is not useful as a medium of entertainment but also useful as a medium in uniting and maintaining inter-ethnic harmony. This study uses qualitative research and uses an ethnographic approach obtained from interviews and uses representation theory by Stuart Hall as a basic analysiis. The conclusion of this research is that Reog art itself is used as a tool to create harmony between the two tribes in Banyuwangi Regency with this Reog art.